2008
DOI: 10.1504/ijtm.2008.015985
|View full text |Cite
|
Sign up to set email alerts
|

Learning mechanisms in a technology based organisational change programme: an exploratory study between Chinese and Norwegian corporations

Abstract: The paper explores how learning mechanisms are adopted and function differently in the course of a managing technology based organisational change programme in Chinese and Norwegian large corporations. We operationalise the abstract organisational learning concepts into a series of learning mechanisms along the change programme implementation process. The results show that national culture, external environment and market status strongly impact the effectiveness of the learning mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In exploring issues of management controls in Chinese SOEs, Ng et al (2009) examined the dilemmas in adopting a contemporary performance measurement system within an SOE as well as the challenges resulting from the power‐centric characteristics of such an SOE when attempting to attain alignment with the diverse interests of stakeholders. Ma et al (2008) further revealed the contradictory learning mechanisms for innovation between Chinese and Norwegian technology‐based organizations. Given these differences in cultural orientations, reverse technology flows by CEMs from an acquired western technology‐based firm might be perplexing due to a paternalistic approach that hinders the dynamism for interactive innovation.…”
Section: Characteristics Of the Chinese Cultural System And Its Influence On Knowledge Flows Within Cemsmentioning
confidence: 99%
“…In exploring issues of management controls in Chinese SOEs, Ng et al (2009) examined the dilemmas in adopting a contemporary performance measurement system within an SOE as well as the challenges resulting from the power‐centric characteristics of such an SOE when attempting to attain alignment with the diverse interests of stakeholders. Ma et al (2008) further revealed the contradictory learning mechanisms for innovation between Chinese and Norwegian technology‐based organizations. Given these differences in cultural orientations, reverse technology flows by CEMs from an acquired western technology‐based firm might be perplexing due to a paternalistic approach that hinders the dynamism for interactive innovation.…”
Section: Characteristics Of the Chinese Cultural System And Its Influence On Knowledge Flows Within Cemsmentioning
confidence: 99%
“…Two other studies have been performed more recently which attempt to examine explicit differences in OL or KM across different firms located in different parts of the world. Ma et al (2008) studied organizations in both China (Eastern and less developed knowledge economy) and Norway (Western and more developed knowledge economy) using a case-based research methodology to analyze differences in OL. They found significant differences between the two countries with respect to who the target of training was, how training was conducted, and when training was conducted.…”
Section: Tlo 156mentioning
confidence: 99%